Treatment of Alopecia Areata and Its Numerous Possibilities: A Literature Review - Wójcik, Julia; Pamuła, Kacper Wojciech; Cholewa, Marcin; Szymańska, Wiktoria Maria; Plewniok, Julia; Partyka, Maria; Jaglarz, Karolina; Kuca, Maciej; Janeczek, Maksymilian; Uchto, Adrian (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Alopecia Areata (AA) is an inflammatory autoimmune disorder characterized by non-scarring hair loss. While it is not life-threatening, it can lead to significant psychological distress. With advancements in modern medicine, new treatments, personalized therapies, and various therapeutic options have emerged. The aim of this study is to review and assess the efficacy, outcomes, and side effects of the available treatment options. Material and methods : To compile this article “PUBMED” and “Google Scholar” databases were used with the great attention given to the articles not older than the year 2018 Brief description of the state of knowledge: There are various treatment options for Alopecia Areata (AA), beginning with topical treatments such as corticosteroids, prostaglandin analogs, minoxidil, and contact immunotherapy. In more severe cases, systemic therapy, biological therapy, or alternative treatments should be considered. Results and conclusions: In the treatment of mild Alopecia Areata (AA), topical therapies are the preferred option due to their minimal side effects and easy to apply nature, with corticosteroids demonstrating the best outcomes, particularly when used in combination therapies. In patients with moderate or severe AA, systemic therapies are recommended, alone or in combination with topical treatment. In patients resistant to other forms of therapy, biological treatments or less commonly used methods should be considered.